(untitled) (Higher Education Politics and Economics, 2023)
The purpose of this convergent parallel mixed-methods instrumental case study was to examine the feasibility of Solar Photovoltaics (PV) as an economic and environmental sustainability tool for higher education while, at the same time, gauging essential university stakeholder knowledge, opinions and beliefs regarding sustainable development, sustainable universities and support for sustainable initiatives on campus. The findings from this study at a Midwestern university indicated that the solar power system generated electricity at a lower cost than the local electric utility was charging and a varied understanding of sustainable development by participants. Implications for provide insight into establishing stakeholder support and a cost/benefit model for sustainable development for institutions of higher learning.